Protestantism and Evangelical churches in Colombia: popular religious practice and belief system - Absalón Jiménez Becerra (methaodos.revista de ciencias sociales, 2014)
<!--[if gte mso 9]> <![endif]--> In this article we tackle the phenomenon of Protestantism in Colombia. In this, we seek to realize the belief system, seen as a relationship of who pretends to the authority, accompanied by an asymmetrical position opposite the believers and practitioners; also, we approached the character of sacred and profane of the belief system, the way hermeneutics and interpretation of various passages of the Bible that, recognized in the Protestant belief system, contributes to the continuous fragmentation of the new religious movements, led by the pentecostal and neopentecostal discourse. Indeed, to understand the phenomenon of popular in Colombia Protestantism, we must realize what happened, from 1991 to date, when constitutional changes provided a number of conditions so that a new religious movement is strengthened. Hence the interest in the present paper, joining a debate that the Academy still not elucidate, and even notes with contempt from our University. <!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->